Equality of Access? Chinese Women Practicing Chan and Transnational Meditation in Contemporary China - Lau, Ngar-Sze (Religions, 2022)
This paper examines how the Buddhist revival, the Chan revival, and recent popularity of transnational meditation practices have facilitated Chinese women practicing Buddhist meditation in contemporary China. With the influence of the opening of China and growing transnational networks, there has been an increasing number of Han Chinese monastics and lay people practicing transnational meditation, such as samādhi, vipassanā and mindfulness, in the past two decades. Despite the restriction of accessing Chan halls at monasteries, some Chinese nuns and laywomen have traveled to learn meditation in different parts of China, and international meditation centers in Southeast Asia to study with yogis from all over the world. Surprisingly some returned female travelers have taken significant roles in organizing meditation retreats, and establishing meditation centers and meditation halls. Through examining some ethnographic cases of Chinese nuns and laywomen, this paper argues that the transnational meditation movement has an impact not only on gender equality, especially concerning Chinese women practicing meditation, but also on the development of contemporary Chinese Buddhism. The significant role of Chinese female meditators in promoting Buddhist meditation can reflect a trend of re-positioning the Chan School in contemporary China.